Prevalence of HIVAb, HbsAg, and HCVAb in Iranian Blood Donors in 2018: A Short Communication - Moslem Soodejani; Ali Akbar Haghdoost; Mohammad Reza Baneshi; Abbas Sedaghat; Seyyed Mohammad Tabatabaei; Farzaneh Zolala (Shiraz University of Medical Sciences, 2023)
Background: The prevalence of infections among general population can affect the prevalence among blood donors. Due to to the importance of blood safety, this study was conducted to estimate the prevalence of HIV, HBV, and HCV in donated bloods in Iran in 2018.Methods: Using information of 1,308,284 blood donors, we designed this cross-sectional study to estimate the prevalence of transfusion-transmitted infections (TTIs) in Iranian blood donors. All the prevalence was reported per 100,000 population.Results: HIV prevalence in blood donors was about 2 per 100,000 (95% CI: 1.999, 2.001) population. Prevalence of HBV and HCV was 53(95% CI: 52.999-53.00) and 26 (95% CI: 25.999-26.001), respectively.Conclusion: It seems that the screening of volunteers would defer many people who may have been infected with TTIs; as a result, people with the least risk of being infected are selected to donate blood. Notice: All of these infected bloods were detected and discarded from the blood donation chain.